Gestión de talento humano en el Comercial Sandrita en el cantón Juján periodo 2021. - Quintana Quijije, Hilary Brigitte (2022)
This case study was carried out in the Sandrita commercial that is located in the Jujan Canton, province of Guayas Jaime roldos Aguilera Street and José Domingo Delgado, directed by Mr. Cujilema Cujilema Sandra Patricia, this is a company dedicated to the retail sale of a wide variety of products such as: products in stores, foodstuffs, beverages or tobacco, among others. This research was made known the shortcomings that arise within the Commercial Sandrita by not having a correct administrative management of the personnel, through which the necessary information was collected in order to develop this case study. According to the information obtained, results were obtained through the problems related to the case, which are: The great dissatisfaction of the clients towards the workers. Keywords. Human talent management, Research,